2012
DOI: 10.4103/0973-6042.96993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of revision biceps tenodesis

Abstract: Purpose:Biceps tenotomy and tenodesis are effective treatment options for biceps pathology, but outcomes of revision surgery are not known. This study examines the clinical outcomes of patients who have undergone a revision biceps tenodesis.Materials and Methods:A retrospective review of all patients since 2004 (N = 21) who had undergone a revision biceps tenodesis with greater than 6-month follow-up was completed. A follow-up survey was carried out, and the visual analog scale (VAS), Single Assessment Numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…For this study, these visits were organized into four follow-up periods based upon the first recorded score within the database (baseline initial assessment): (1) 3-mo follow-up (80 to 100 d after initial assessment); (2) > 3-mo follow-up (90 d or more after initial assessment); 6-mo follow-up (170 to 190 d after initial assessment); and (3) > 6-mo follow-up (180 d or more after initial assessment). These follow-up periods were selected based upon recommendations within the literature[ 27 - 37 ]. It should be noted that the baseline score may not necessarily correlate with a specific intervention.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, these visits were organized into four follow-up periods based upon the first recorded score within the database (baseline initial assessment): (1) 3-mo follow-up (80 to 100 d after initial assessment); (2) > 3-mo follow-up (90 d or more after initial assessment); 6-mo follow-up (170 to 190 d after initial assessment); and (3) > 6-mo follow-up (180 d or more after initial assessment). These follow-up periods were selected based upon recommendations within the literature[ 27 - 37 ]. It should be noted that the baseline score may not necessarily correlate with a specific intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Follow‐up time‐periods of 3‐ and 6‐month were selected to correspond with commonly used follow‐up periods in prior orthopaedic literature and clinical practice . Three‐ and six‐months and beyond follow‐up periods were used in addition to these narrowly defined time‐periods to broaden the catchment time‐frame to include the full‐range of patients seeking follow‐up care, also seen in prior literature . Paired sample t ‐tests evaluated the hypothesis that no change occurred between baseline and each follow‐up time point.…”
Section: Methodsmentioning
confidence: 99%
“…[39][40][41][42][43] Three-and six-months and beyond follow-up periods were used in addition to these narrowly defined time-periods to broaden the catchment time-frame to include the full-range of patients seeking follow-up care, also seen in prior literature. [44][45][46] Paired sample t-tests evaluated the hypothesis that no change occurred between baseline and each follow-up time point. The significance level was set at 0.05, two sided.…”
Section: Analytic Approachmentioning
confidence: 99%
“…In fact, high rates of good to excellent clinical outcomes have been reported following surgical treatment using the IS fixation technique with small occurrence of fixation failure (Mazzocca et al, 2008;Nho et al, 2010). However, some complications have been reported after tenodesis with IS such as persistent bicipital pain or even bone fracture (Gregory et al, 2012;Mazzocca et al, 2008;Sears et al, 2011). Moreover, in open surgery, neurovascular injury or infection (Ma et al, 2009;Nho et al, 2010) has been reported.…”
Section: Introductionmentioning
confidence: 94%